A rare cause of neonatal hypertension: Congenital mesoblastic nephroma - Soyaltın, Eren; Alaygut, Demet; Alparslan, Caner; Özdemir, Tunç; Çamlar, Seçil Arslansoyu-; Mutlubaş, Fatma; Kasap-Demir, Belde; Yavaşcan, Önder (The Turkish Journal of Pediatrics, 2018)
A rare cause of neonatal hypertension: Congenital Mesoblastic Nephroma (CMN) is a rare renal tumor in childhood and has been reported with palpable abdominal mass, hypertension, hematuria, polyuria and hypercalcemia. Histopathologically it has been classified into two histological types: classic and cellular. We present a 32-week gestation infant and his histopathology reports of cellular CMN presented with refractory hypertension.
Keywords: hypertension; mesoblastic nephroma; newborn